Kinetic Study And Isoterm Adsorption Of Pb Metal In Ouw Village Clay Activated Ammonium Nitrate Salt - Sekewael, Serly J.; Tehubijuluw, Hellna; Reawaruw, Delvika R. (Indonesian Journal of Chemical Research, 2013)
Kinetics studies and adsorption isotherms of Pb metal have been conducted on activated clay salts of ammonium nitrate (NH4NO3). Clays used are taken from Ouw village, Central Maluku. Clay activated by soaking in a solution of NH4NO3 700 ppm for 5 hours, then filtering and heating in a furnace at 550 oC for 4 hours. The optimum adsorption of metal ions Pb (II) by activated clay ammonium nitrate occurs at pH 4 with a contact time of 4 hours and followed the Freundlich adsorption isotherm pattern with a Kf value of 1.6193 x 10-8 mg/g and n value of 0.2059. Pb adsorption kinetics followed the pseudo-second-order Lagergren equation with the value of the adsorption rate constant (k2, ads) of 0.1248 g mg-1 min-1 and Xe value of 4.4783 mg/g.